Medical Liability of Residents in Taiwan Criminal Court: An Analysis of Closed Malpractice Cases. (1st June 2020) - Wu, Kuan-Han; Chuang, Po-Chun; Su, Chih-Min; Cheng, Fu-Jen; Wu, Chien-Hung; Chen, Fu-Cheng; Huang, Yii-Ting
Abstract : Objective . By analyzing closed criminal malpractice claims involving resident physicians, we aimed to clarify the characteristics of litigations and examine the litigious errors leading to guilty verdicts. Design . A retrospective descriptive study. Setting/Study Participants . The verdicts pertaining to physicians recorded on the national database of the Taiwan justice system were reviewed. Main Outcome Measures . The characteristics of litigations were documented. Negligence and guilty verdicts were further analyzed to identify litigious errors. Results . Between January 1, 2000, and December 31, 2014, from a total of 436 closed criminal malpractice cases, 40 included resident physicians. Five (12.5%) cases received guilty verdicts with mean imprisonment sentences of 5.4 ± 4.1 months. An average of 77.2 months was required for the final adjudication, and surgery residents were involved most frequently (38.9%). Attending physicians were codefendants in 82.5% of cases and were declared guilty in 60% of them. Sepsis (37.5%) was the most common disease in the 40 cases examined, followed by operation/procedure complications (25%). Performance errors (70%) were more than twice as common than diagnostic errors (30%), but the percentage of guilty verdicts in performance error cases was much lower (7.1% vs. 25%). Four negligence cases received nonguilty verdicts, which were mostly due to lack of causation. Conclusion . Closed criminal malpractice cases involving residents took on average 6.22 years to conclude. Performance errors accounted for 70% of cases, with treatment of sepsis and operation/procedure complications predominant. To reduce medicolegal risk, residents should learn experiences from analyzing malpractice cases to avoid similar litigious pitfalls.